Regional Response of Low Carbon Investments to the COVID-19 Pandemic: The Case of Stock Markets in Seeking Carbon Neutrality Goals - Chen, Jiang; Zhao, Long; Teresienė, Deimantė; Keliuotytė-Staniulėnienė, Greta; Budrienė, Daiva; Kanapickienė, Rasa; Kartasova, Jekaterina; Gu, Jianqiang (Frontiers in Environmental Science, 2022)
Sustainable and responsible investments (SRI) are a very important area in the field of climate change and sustainable economic growth. The research considers the impact of the COVID-19 pandemic on SRI using Environmental, Social, and Governance (ESG) factors in different regions to find the correlation between various markets and the impact of the pandemic on SRI. Our research employed the method of covariance/correlation analysis to investigate the relationship between SRI in different regions. We also checked the main parameters of descriptive statistics and used the method of bivariate regression analysis to assess the impact of the COVID-19 pandemic on the performance of ESG stock indices in Emerging, European, and Global markets. The main findings revealed that the global prevalence and mortality risk of COVID-19 infection have a significant negative effect on the performance of Emerging, European, and Global ESG stock markets, while the effect of COVID-19 cases reported as well as deaths caused by COVID-19 infection appeared to be mixed. Our research showed that in the one-year horizon, the correlation between the European ESG stock market and other ESG markets was exceptionally low or negative, while tendencies in other markets were similar. So it means that the European ESG stock market is a good tool for diversification and risk mitigation during critical moments. Our results can be used in practice for portfolio management purposes. Institutional and other investors can use these results for SRI portfolio management and risk mitigation.